A cross-sectional study of docosahexaenoic acid status and cognitive outcomes in females of reproductive age with phenylketonuria - Yi, Sarah H. L. (J Inherit Metab Dis, 2011)
Diet therapy for phenylketonuria (PKU) requires restricted phenylalanine (Phe) intake, with the majority of protein and other nutrients coming from synthetic medical food. The fatty acid docosahexaenoic acid (DHA) is important in brain development and function; however, there are reports of low blood DHA concentrations in people treated for PKU. Although the implications of this low blood DHA are unclear, subtle cognitive deficits have been reported in those treated early and continuously for PKU. For this study, we investigated the relationship between DHA status and cognitive performance in 41 females 12 years and older with PKU. Participants were attending the baseline visit of a research-based camp or a supplementation trial. We assessed the domains of verbal ability, processing speed, and executive function using standardized tests, and the proportions of DHA in plasma and red blood cell (RBC) total lipids using gas chromatography/mass spectrometry. Percent plasma and RBC total lipid DHA were significantly lower in the participants compared with laboratory controls (P < .001), and participants consumed no appreciable DHA according to diet records. Plasma and RBC DHA both negatively correlated with plasma Phe (P < .02), and performance on the verbal ability task positively correlated with RBC DHA controlling for plasma Phe (R=.32, P=.03). The relationship between DHA and domains related to verbal ability, such as learning and memory, should be confirmed in a controlled trial. Domains of processing speed and executive function may require a larger sample size to clarify any association with DHA.